Comparative study the morphology of gill rakers and the diameters of Red and White muscle fibers of two types of the native teleosts - J. Mansour, Akeil; Y. Awad, Emad; G. Talip, Saja (Al-Qadisiyah Journal of Pure Science, 2018)
The present study deals with comparative study of Two species of teleosts which belong to the different two families Ø›the first is Liza abu(Heckel,1864 )that belong to the Muguilidea and the second is Cyprinus carpio(L.)which belong to the Cprinidea,In order to study morphometrics of gill rakers and evaiute of filteration area of gill rakers,study some histological featurea of the diameters of red and white muscle fibers as well. Samples are collected from aquaculture stations of marine science centre of BasrahUniversity.These samples are between Desemper/2011 to Feberuary/2012. The Current results showed differences of the studied species in shapes and numbers of gills rakers,L.abuhas longer, thiner gill rakers and possesses (34-60 gill rakers),while the C.carpiopertain small,shorter and has (20-38 gill rakers).Beside,these results showed that different of studied species in values of the filteration areas L.abuhas(19-54 mm2) while the C.carpiohas (9-30 mm2)The results especially in the diameters of red and white muscle fibers between the studied species showØŒs differ in shape,size and dimeter of muscle fibers.the red muscle fibers were giobularfibers,smallsize,homologenous fibers and diameters ranged between (20-42 micro)in Liza abualso ranged between (14-40 micron) inC.carpio,while the white muscle fibers were irregualar fibers, heterogenousfibers,and the diameters were ranged between (40-74 micron)in L.abu while were ranged between (32-64 micron) in C.carpio.These results are discussed on the bases of the functional role to the red and white muscle fibers.